Experimental Study on MR Signal Intensity Changes with the Degree of Calcification - MATSUMOTO, Ko; SAKAMOTO, Maya; IIKUBO, Masahiro; SASANO, Takashi; SUGAWARA, Yumiko; SAITO, Mikiko (Shika Hoshasen, 2004)
Purpose: To investigate how the signal intensity changes with the progress of calcification on T1-weighted (T1W) MR and CT images. Materials and methods: As a calcified material, HA (hydroxyapatite) alone, DCPD (dicalcium phosphate dehydrate) alone and DCPD-HA mixture in equal volume (as intermediate calcification) were used. Nine different weights of each material (0∼16g) were mixed with agar solution in the bottle, and then, each bottle, containing a different calcified material with a different density, was placed in the plastic case filled with distilled water. T1W images of all phantoms were obtained with the spin echo technique using 1.5T MR system. The signal intensity ratio (SIR) of calcium phosphate in each bottle to the surrounding distilled water was measured in all the phantoms. On CT examination, the CT number of calcium phosphate in each bottle was measured. Results: On DCPD and HA, SIR showed an increase with the concentration in the low to intermediate concentration, however they decreased in the higher concentration. On DCPD-HA mixture, SIR showed an immediate increase at the lowest concentration (2g), and was sustained at the middle level until the highest concentration. SIR showed a higher value in the more contained hydrate material in the low to intermediate concentration, however, the apparent relationship between hydrate in calcification and SIR could not be found in the high concentration. The CT number of each material increased with the calcium concentration in all phantoms, i. e., CT number was the highest in HA and the lowest in DCPD. Conclusion: MR signal intensity on T1WI of calcified materials changes not only with calcium concentration but with hydrarte in the calcification.